MENINGKATKAN PRESTASI BELAJAR SOSIOLOGI MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA PESERTA DIDIK KELAS XI MIPA 4 SMA NEGERI 8 PONTIANAK - Partiwi, Sri Uji (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
This study aims to determine whether these students have mastered the learning material that has been taught is by increasing students' learning achievement in sociology, where the facts on the ground show that student achievement in sociology subjects is still low. Thus, the teacher took the initiative to use a learning model that is not commonly used in the classroom, namely using the Problem Based Learning (PBL) learning model. Methods in this study Approach This research uses a quantitative qualitative approach. The instruments in this study were test questions, slow observation, interview guides, and questionnaires. After using the Problem Based Learning (PBL) Model for students of class XI MIPA 4 SMA Negeri 8 Pontianak, the learning achievement of most students in learning increased. This is known from students who are far more students listening to the material presented by the teacher, seem enthusiastic in participating in sociology learning material on social problems and their impact on people's lives, expressing their opinions, asking about things that are not known, and working in groups with other friends. . In addition, it can be seen from the results of observations that show a score of 60. This means that the activity of students in the class is quite good. The results of observations in cycle 1 showed a score of 119. This means that the activity of students in the class is quite good. However, in order to be more conducive to learning sociology of social change material and its impact on people's lives, the researcher wants to carry out the second cycle, the observations show a score of 153. This means that the activity of students in the classroom is very good.